Specific features of clinical support of depressive disorders under conditions of chronic war-related stress using a clinical case study - Zubatiuk, Оксана; Bashynskyi, Олександр (Psychosomatic Medicine and General Practice, 2025)
Relevance. The impact of war-related stress in Ukraine, now approaching the period of four years, is a significant factor influencing mental health in general and the development of depressive disorders in particular. Studying the clinical and psychopathological features of depression under conditions of chronic war-related stress is essential for developing more effective treatment and rehabilitation strategies. Objective. To examine the clinical and psychopathological features of depressive disorders under prolonged exposure to war-related stress using a specific clinical case, and to determine the peculiarities of clinical support. Methods and materials. Study and analysis of a clinical case involving a female patient with anxiety-depressive symptoms under chronic war-related stress, with attention to the clinical and psychopathological characteristics of the symptoms, their course and dynamics, as well as the effectiveness of therapeutic approaches. Results. Chronic war-related stress in Ukraine constitutes a major psychotraumatic factor, characterized by fear for one’s own life and the lives of close ones. This represents a high-intensity stressor which, given that the war has entered its fourth year, has become chronic in nature. This requires more in-depth research into the clinical and psychopathological features of disorders developing under these conditions, including adjustment disorders, anxiety disorders, and depressive disorders. Both direct manifestations of chronic war-related stress (fear for one’s own life and the lives of close ones) and indirect ones (significant lifestyle changes such as forced separation from partners, financial instability, and uncertainty about the future) act as aggravating factor for the psyche that shortens remission duration and contributes to recurrence of depressive symptoms. The complex clinical pathomorphosis of depressive symptoms under the influence of psychogenic factors associated with chronic war-related stress requires a review of treatment approaches, particularly regarding the duration of medical therapy and the timing and clinical criteria for its withdrawal. Conclusions. Under conditions of chronic war-related stress, certain specific features are observed in the clinical presentation of depressive syndromes within affective disorders, and these require further investigation. Accounting for the clinical pathomorphosis of depressive disorders under the influence of a major stressogenic factor — the war in Ukraine, now ongoing for a fourth consecutive year — will facilitate the improvement of existing approaches to treatment, rehabilitation, and prevention of affective disorders. Keywords: depressive disorders; adjustment disorders; chronic war-related stress; diagnosis and treatment of mental disorders